2008
DOI: 10.1017/s0025315408001276
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of macrofaunal assemblages along the English Channel

Abstract: The present study investigates the species distribution patterns and macrofaunal assemblages along the English Channel and the environmental factors contributing to observed patterns. Seven distinct macrofaunal assemblages were identified based on Hamon grab samples. In the western Channel, an Echinocyamus/Nemertea assemblage dominated, giving way to an Abra/Scalibregma assemblage in inshore waters. A Verruca/Sabellaria assemblage was identified to occupy large regions of the mid-Channel while those of the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…The communities sampled in the Wash and Wight regions demonstrated high abundance and biomass per grab (Table I) and were characterized by very different assemblages compared to the other regions in this study. The higher species diversity in the Wash and Wight compared to other regions of the English Channel have been noted previously (Tappin et al , 2011) and is probably explained by differences in sediment type, depth, turbidity, temperature and tidal stress (Bolam et al , 2008). The dominance of Crepidula spp.…”
Section: Discussionsupporting
confidence: 61%
“…The communities sampled in the Wash and Wight regions demonstrated high abundance and biomass per grab (Table I) and were characterized by very different assemblages compared to the other regions in this study. The higher species diversity in the Wash and Wight compared to other regions of the English Channel have been noted previously (Tappin et al , 2011) and is probably explained by differences in sediment type, depth, turbidity, temperature and tidal stress (Bolam et al , 2008). The dominance of Crepidula spp.…”
Section: Discussionsupporting
confidence: 61%
“…This is due to an increased number of species able to live at each of the depth zones, producing a homogenization in the composition of the assemblage along the depth gradient and the loss of exclusive species. Problems of biotic homogenization driven by climate change have already been discussed in recent papers, even for the marine environment (Olden & Rooney 2006; Bolam et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 693 taxa (546 non-colonial and 147 colonial) was sampled, leading to the identification of seven assemblages: A) Echinocyamus/Nemertea; B) Verruca/Sabelleria spinulosa; C) Balanus/Spiophanes; D) Echinocyamus/Polycirus; E) Distomus/Balanus; F) Abra/Scalibregma and G) Nephtys-Bathyporeia. Bolam et al (2008) stressed that the biological communities do not exhibit any E-W differentiation, even though their study includes a relatively low number of stations. reported that the distribution of sediment type and benthic communities was polarised around a distinctive local hydrodynamic feature in the centre of their sampling transect from 3°W to 3°E using a large dataset of samples in the vicinity of the Isle of Wight and the Cotentin Peninsula.…”
Section: Recent Benthic Studies On the English Sidementioning
confidence: 96%
“…Several taxa (echinoderms, polychaetes, bivalves and crustaceans) decline immediately after trawling and are shown to have recovered six months later. Bolam et al (2008) have described the spatial distribution of assemblages along the whole English side of the EC from grounds off Plymouth to the Dover Strait using a 0.1 m 2 Hamon grab on 31 stations using the CEFAS vessel fitted with a dynamic global positioning system. In addition to grab samples, multibeam acoustic data have been obtained for each station.…”
Section: Recent Benthic Studies On the English Sidementioning
confidence: 99%